Persecuzioni religiose e diritto d’asilo nella giurisprudenza delle Corti sovranazionali europee (Stato, Chiese e pluralismo confessionale, 2014)
Il contributo, sottoposto a valutazione, è destinato alla pubblicazione in“International Religious Freedom and The Global Clash of Values/La libertà religiosa secondo il diritto internazionale e lo scontro global dei valori, Proceedings of the conference held in Rome, 20-21 June 2014/Atti del convegno svoltosi a Roma il 20 e 21 giugno 2014”.SOMMARIO: 1. Introduzione - 2. Divieto di tortura e persecuzioni religiose nella giurisprudenza della Corte Europea dei Diritti dell’Uomo – 3. La nozione di persecuzione religiosa nella giurisprudenza della Corte di Giustizia dell’Unione europea e divergenza rispetto alla Corte di Strasburgo – 4. Conclusioni. ABSTRACT: Religious Persecutions and Asylum Law in the case law of European Supranational CourtsThe rise of restrictions on religious freedom, resulting in the denial of fundamental rights in many parts of the world, has caused an increase in asylum requests in many European countries. This article compares and contrasts the approaches of the European Court of Human Rights and the Court of Justice of the European Union, highlighting common approaches and divergences. Part I introduces the topic. Part II discusses the case law of the European Court of Human Rights. Part III compares and contrasts the approach of the Strasbourg Courts with a recent decision of the Court of Justice of the European Union. Part V concludes arguing for the need of further development of the case law of the European Court of Human Rights in line with the recent developments in EU law.